Autoimmunity, Seizures and Epilepsy: A Brief Systematic Review [Autoinmunidad, Convulsiones y Epilepsia: Breve Revisión Sistemática] - Labbe-Atenas, T (Sociedad de Neurologia Psiquiatria y Neurocirugia, 2021)
Epilepsy is a neurological chronic disorder which is characterized by recurrent seizures and constitutes one of the most prevalent neurological disorders worldwide. One of the etiologies that has gained a lot of strength is autoimmunity, which has explained a lot of cases of idiopathic epilepsy or epilepsies refractory to common treatment. Methods: An advanced search was made in the PubMed platform using filters with the terms "epilepsy" and "autoimmunity", showing 98 publications from 2010 onwards, leaving only 17 selected articles because of their pathophysiological information. Results: Based on the literature, we described the main mechanisms of autoimmunity as a cause of epilepsy, standing out the ones related to auto-antibodies production, cytokines disregulation and autoreactive T lymphocytes control alteration, phenomenons related to neuroinflammation that arise from the context of infections, paraneoplastic syndromes, maternal autoimmunity transmitted to their babies, autoimmune encephalitis, etc. Conclusions: Great advances has been made on the understanding of autoimmune epilepsy in the last years, but despite this there’s a lot that we need to comprehend. Although how promising was the discovery of antibodies there’s still a lot of seronegative cases or cases with antibodies but without the epilepsy. It is worth mentioning that it becomes necessary to establish efficient and specific diagnostic mechanisms that allow us to create suitable and resolutive therapeutic protocols. © 2021 Sociedad de Neurologia Psiquiatria y Neurocirugia. All rights reserved.